Shallow Creep Along the 1999 Izmit Earthquake Rupture (Turkey) From GPS and High Temporal Resolution Interferometric Synthetic Aperture Radar Data (2011-2017) - Aslan, Gokhan; Lasserre, Cecile; Cakir, Ziyadin; Ergintav, Semih; Ozarpaci, Seda; Dogan, Ugur; Bilham, Roger; Renard, Francois (AMER GEOPHYSICAL UNION, 2019)
Characterizing the spatiotemporal evolution of creep is essential to constrain fault slip budget and understand creep mechanism. Studies based on interferometric synthetic aperture radar and Global Positioning System (GPS) satellite observations until 2012 have shown that the central segment of the 17 August 1999 M-w 7.4 Izmit earthquake on the North Anatolian Fault began slipping aseismically following the event. In the present study, we combine new interferometric synthetic aperture radar time series, based on TerraSAR-X and Sentinel 1A/B radar images acquired over the period 2011-2017, with near-field GPS measurement campaigns performed every 6months from 2014 to 2016. The mean velocity fields reveal that creep on the central segment of the 1999 Izmit fault rupture continues to decay, more than 19years after the earthquake, in overall agreement with models of postseismic afterslip decaying logarithmically with time for a long period of time. Along the fault section that experienced supershear velocity rupture during the Izmit earthquake creep continues with a rate up to 8mm/year. A significant transient accelerating creep is detected in December 2016 on the Sentinel-1 time series, near the maximum creep rate location, associated with a total surface slip of 10mm released in 1month only. Additional analyses of the vertical velocity fields show a persistent subsidence on the hanging wall block of the Golcuk normal fault that also ruptured during the Izmit earthquake. Our results demonstrate that afterslip processes along the North Anatolian Fault east-southeast of Istanbul are more complex than previously proposed as they vary spatiotemporally along the fault.
Keywords: InSAR; aseismic slip; creep; Izmit; Turkey; GPS; NORTH ANATOLIAN FAULT; SAN-ANDREAS-FAULT; STRAIN ACCUMULATION; HAYWARD FAULT; SPATIOTEMPORAL EVOLUTION; INSAR OBSERVATIONS; ISMETPASA SEGMENT; SURFACE CREEP; HAIYUAN FAULT; Geochemistry & Geophysics